Influence of biofilm composition on the resistance to detachment - Simões, M. (2007)
Bacillus cereus and Pseudomonas fluorescens were used to develop monoculture biofilms in a bioreactor rotating system using a stainless steel cylinder for biofilm formation. The biofilms were allowed to grow for 7 days, exposed continuously to a Reynolds number of agitation (ReA) of 2,400. Afterwards, the biofilms were characterised in terms of respiratory activity, amount of biomass, cellular density, cellular size and total and extracellular proteins and polysaccharides. The biofilm mechanical stability was assessed by sequential submission of the biofilms to increasing ReA, respectively, 4,000, 8,100, 12,100 and 16,100. The results showed that P. fluorescens biofilms were five times more active, had a higher amount of biomass, cellular density, a reduced cellular size and a four-fold higher amount of extracellular proteins and polysaccharides than B. cereus biofilms. The application of shear stress forces higher than the one under which the biofilm was formed (ReA ¼ 2,400) caused biomass removal. The high percentage of removal occurred with the implementation of a ReA of 8,100 for both B. cereus and P. fluorescens biofilms. The total series of ReA did not give rise to total biofilm removal, as only about 76% of P. fluorescens biofilm mass and 53% of B. cereus biofilm mass were detached from the cylinders. This latter result evidences that B. cereus had a higher mechanical stability than P. fluorescens biofilms. The overall results demonstrate that P. fluorescens and B. cereus formed physiologically distinct biofilms, B. cereus biofilms mainly being constituted by cells and P. fluorescens biofilms largely constituted by extracellular proteins and polysaccharides. B. cereus biofilms had a substantially higher mechanical stability than P. fluorescens biofilms.